Parametric Study Of Broadband Inverted Suspended Linear Polarized Antenna - Phoo, Kho Shin; Abd Aziz, Mohamad Zoinol Abidin; Othman, Mohd Azlishah; Suaidi , Mohamad Kadim; Mohamad@Sulaiman, Hanissah; F., Abd. Malek (Asian Research Publishing Network (ARPN), 2015)
In this paper, the parametric study of a broadband inverted suspended rectangular patch with rectangular slot which performed as linear polarized antenna is presented. The operating frequency for the proposed antenna is at 2.4GHz, which is for Wireless Local Area Network (WLAN) application. The performances for the proposed linear polarized antenna are investigated with the variation of different design parameters, which included the width of rectangular slot, X,length of rectangular slot, Y, separation of strip line from rectangular slot, A, and thickness of air gap, Gap. This antenna is designed by using method of inverted suspended, where the copper ground plane and the inverted rectangular patch is separated with air gap. This technique is used to enhance to bandwidth and gain of the proposed antenna. The simulation is done using Computer Simulation Technology (CST) software. The performance of linear polarization antenna can be verified based on the axial ratio result, where the axial ratio for linear polarized antenna is above 3dB.